S58 Surfactant Phospholipid Kinetics in Patients with Acute Respiratory Distress Syndrome (ARDS). (19th November 2012) - Dushianthan, A; Cusack, R; Goss, V; Grocott, MPW; Postle, AD
Abstract : Introduction and Aims: ARDS is a significant health burden. Mortality still remains high between 30–50%. Surfactant is a mixture of phospholipids and proteins. Phosphatidylcholines (PC) account for 80% of total phospholipids. PC16:0/16:0 is the main PC with surface tension reducing characteristics. Surfactant abnormalities are well recognised in patients with ARDS However, replacement strategies remain unhelpful in improving mortality. Existing diagnostic definitions fail to identify a homogeneous population and this lack of phenotyping of patients according to surfactant biology may in part explain the absence of therapeutic benefit. The aims of this study are to assess surfactant PC kinetics by the incorporation of methyl -D9 -choline in patients with ARDS. Methods: ARDS patients were identified according to American European Consensus Conference (AECC) criteria. Patients were infused with 3.6mg/kg methyl -D9-choline. Small volume bronchoalveolar lavages were performed via a fibre optic bronchoscope at serial time points. Healthy volunteers were used as controls. The phospholipid fraction was extracted and analysed by triple quadrupole electrospray ionisation mass spectrometry. Results: Ten patients and nine healthy controls were recruited. The endogenous PC composition consisted primarily of PC16:0/16:0, PC16:0/18:1 and PC18:0/18:2. There was significant reduction in the relative proportion of endogenous PC16:0/16:0 in patients. Compared to healthy controls, newly synthesised deuteriated PC16:0/16:0 was much lower in patients (26%) than controls (47%). Total surfactant PC D9 - incorporation was linear until 48 hours (0.019%/h, r 2 =0.9734, P<0.05) and reached its maximum at 48 hours (0.93±0.15%). Steady state of incorporation was achieved between 48–96 hours. There was ∼80% increase in the fractional D9 labelling in patients at 48 hours compared to healthy controls. Total plasma PC D9 -incorporation was linear until 24 hours (0.032%/h, r 2 =0.9825, P<0.05) and reached its maximum (0.755±0.056%) at 24 hours. Linear decline in enrichment was noted after 24 hours at a rate of 0.003% per hour (r 2 =0.9915, P<0.05). The total surfactant PC D9 -incorporation was much higher for patients at 24 hours and 48 hours reflecting increased synthetic rate. Conclusions: By labelling surfactant PC precursors, it is possible to study surfactant kinetics in patients with ARDS. The methodology may be utilised to phenotype patients according to alveolar surfactant kinetics prior to replacement strategies.